2022
DOI: 10.1016/j.ebiom.2022.103824
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization study on the causal effects of tumor necrosis factor inhibition on coronary artery disease and ischemic stroke among the general population

Abstract: Background Tumor necrosis factor (TNF) is a potent inflammatory cytokine that has been causally associated with coronary artery disease (CAD) and ischemic stroke (IS), implying opportunities for disease prevention by anti-TNF therapeutics.Methods Leveraging summary statistics of several genome-wide association studies (GWAS), we assessed the repurposing potential of TNF inhibitors for CAD and IS using drug-target Mendelian randomization (MR) design. Pharmacologic blockade of the pro-inflammatory TNF signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…For example, a REGARDS cohort study suggested that IL6 was the only inflammatory cytokine to be strongly associated with the risk of stroke ( Jenny et al, 2019 ); a meta-analysis revealed that higher circulating IL6 levels are associated with higher long-term risk of incident IS independent of conventional vascular risk factors ( Papadopoulos et al, 2021 ). TNF was reported to be produced by microglia and leukocytes in ischemic stroke tissue and plasma TNF receptor 1 (TNFR1) and TNFR2 target post-stroke inflammation could be a promising adjunctive therapy for IS patients ( Clausen et al, 2020 ); however, Kang X et al held a different view that no protective effect of TNF/TNFR1 inhibition on IS was observed through drug-target Mendelian randomization ( Kang et al, 2022 ). Although the function of PI3K, IL6 and TNF in neuroinflammation after IS needs further investigation, the above information is sufficient to convince us that they play a key role in neuroinflammation after IS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a REGARDS cohort study suggested that IL6 was the only inflammatory cytokine to be strongly associated with the risk of stroke ( Jenny et al, 2019 ); a meta-analysis revealed that higher circulating IL6 levels are associated with higher long-term risk of incident IS independent of conventional vascular risk factors ( Papadopoulos et al, 2021 ). TNF was reported to be produced by microglia and leukocytes in ischemic stroke tissue and plasma TNF receptor 1 (TNFR1) and TNFR2 target post-stroke inflammation could be a promising adjunctive therapy for IS patients ( Clausen et al, 2020 ); however, Kang X et al held a different view that no protective effect of TNF/TNFR1 inhibition on IS was observed through drug-target Mendelian randomization ( Kang et al, 2022 ). Although the function of PI3K, IL6 and TNF in neuroinflammation after IS needs further investigation, the above information is sufficient to convince us that they play a key role in neuroinflammation after IS.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we detected 3 other SNPs (rs767455, rs4149570, and rs4149577) in the targeted gene that are associated with CRP levels and had previously been utilized in studies aiming to evaluate the effect of genetically proxied TNFR1 inhibition on several disease outcomes. In these MR studies, the indexing of TNF-TNFR1 signaling inhibition utilizing these 3 SNPs showed protective effects for diseases where TNF inhibitors have been approved for treatment, and unfavorable outcomes where TNF inhibitors are known to exacerbate the symptoms ( 31 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…We selected TNFR1, CRP, and WBC as the indicators of TNF inhibition, because TNFR1 was the direct target of inhibition of SNPs, which can be observed to examine the effect of the selected SNPs. In addition, CRP and WBC were the classical downstream targets of TNF signaling, and they were Frontiers in Pharmacology frontiersin.org also used as indicators of TNF inhibition in the previously published mendelian randomization studies (Kang et al, 2021(Kang et al, , 2022. We selected the SNPs that were associated with the decrease in the three biomarkers, and we specifically chose CRP as a proxy instrument to detect the magnitude of the inhibitory effect, because of its vital role in the TNF signaling pathway and its specific measurement in the GWAS study-measured as natural-log transforms of mg/L.…”
Section: Selection Of Instrumental Variablesmentioning
confidence: 99%
“…We selected the SNPs that were associated with the decrease in the three biomarkers, and we specifically chose CRP as a proxy instrument to detect the magnitude of the inhibitory effect, because of its vital role in the TNF signaling pathway and its specific measurement in the GWAS study-measured as natural-log transforms of mg/L. The SNPs that caused reductions in all three biomarkers were included, and we used a cut-off point of p < 0.05 for significant associations and stringent criteria of linkage disequilibrium (r2<0.001) to further screen the SNPs, as reported in previous studies (Schmidt et al, 2020;Kang et al, 2021Kang et al, , 2022.…”
Section: Selection Of Instrumental Variablesmentioning
confidence: 99%
See 1 more Smart Citation